A novel DNMT1 mutation associated with early onset hereditary sensory and autonomic neuropathy, cataplexy, cerebellar atrophy, scleroderma, endocrinopathy, and common variable immune deficiency. Issue 3 (September 2016) - Fox, Robin; Ealing, John; Murphy, Helen; Gow, David P.; Gosal, David
Abstract: DNA methyltransferase 1 ( DNMT1 ) is an enzyme which has a role in methylation of DNA, gene regulation, and chromatin stability. Missense mutations in the DNMT1 gene have been previously associated with two neurological syndromes: hereditary sensory and autonomic neuropathy type 1 with dementia and deafness (HSAN1E) and autosomal dominant cerebellar ataxia, deafness, and narcolepsy (ADCA‐DN). We report a case showing overlap of both of these syndromes plus associated clinical features of common variable immune deficiency, scleroderma, and endocrinopathy that could also be mutation associated. Our patient was found to be heterozygous for a previously unreported frameshift mutation, c.1635_1637delCAA p.(Asn545del) in the DNMT1 gene exon 20. This case displays both the first frameshift mutation described in the literature which is associated with a phenotype with a high degree of overlap between HSAN1E and ADCA‐DN and early age of onset (c. 8 years). Our case is also of interest as the patient displays a number of new non‐neurological features, which could also be DNMT1 mutation related.